Modelling the effect of the introduction of antenatal screening for group B Streptococcus (GBS) carriage in the UK. Issue 3 (23rd March 2019) - Bevan, David; White, Alicia; Marshall, John; Peckham, Catherine
Abstract : Objectives: To estimate the potential impact of the addition of culture-based screening for group B streptococcus (GBS) carriage in pregnancy to a risk-based prevention policy in the UK. We aimed to establish agreement within a multidisciplinary group of key stakeholders on the model input parameters. Design: Deterministic model using a consensus approach for the selection of input parameters. Setting and participants: A theoretical annual cohort of 711 999 live births in the UK (excluding births by elective caesarean section). Interventions: Culture-based screening for GBS at 35–37 weeks of pregnancy added to the recommended risk-based prevention policy in place on the date of modelling. Outcome measures: Outcomes assessed included use of intrapartum antibiotic prophylaxis (IAP), early onset GBS (EOGBS), EOGBS mortality, severe EOGBS-related morbidity and maternal penicillin anaphylaxis. Results: With no prophylaxis strategy, the model estimated that there would be 421 cases of culture positive EOGBS in a year (0.59/1000 live births). In the risk-based prophylaxis scenario, 30 666 women were estimated to receive IAP and 70 cases of EOGBS were prevented. Addition of screening resulted in a further 96 260 women receiving IAP and the prevention of an additional 52 to 57 cases of EOGBS. This resulted in the prevention of three EOGBS deaths and four cases of severe disability. With screening, an additional 1675 to 1854 women receive IAP to prevent one EOGBS case and 24 065 to 32 087 receive IAP to prevent one EOGBS death. Conclusions: The evidence base available for a broad range of model input parameters was limited, leading to uncertainty in the estimates produced by the model. Where data was limited, the model input parameters were agreed with the multidisciplinary stakeholder group, the first time this has been done to our knowledge. The main impact of screening is likely to be on the large group of low-risk women where the clinical impact of EOGBS tends to be less severe. This model suggests that the reduction in mortality and severe disability due to EOGBS with antenatal GBS screening is likely to be very limited, with a high rate of overdetection and overuse of antibiotics.